Zespół Gregga jako wyzwanie dla teorii i praktyki logopedycznej. Studium przypadku - Minczakiewicz, Elżbieta Maria (Logopedia Silesiana, 2012)
Gregg’s team as a challenge to the theory and practice speech therapy. Case StudyThis article is an attempt to share their experiences obtained in the course of speech therapywork with children profoundly handicapped, which soon after thorough clinical diagnosis changed,calling them children of a team of Gregg. The first part of article I described is relatively rare occurringin children, with different symptoms disorder caused by rubella virus. Looking for an answer to thequestion about the nature of the disorder, concentrated on specialist literature and the results of theirown trials and speech therapy practice. In the second part of the paper I decided to share their experiencesthose obtained step by step on how to work with them – as children with a diagnosis of Gregg’steam. For example, the selected case study – I tried to show the results of speech therapy struggle. However,the results of several multi-profile treatment of the interesting group of people with a diagnosis ofGregg, I treated as a new challenge to the theory and practice of speech therapy.